Analysis of the national transplant scenario in Brazil (Research, Society and Development, 2023)
The objective of the study was to analyze the panoramic scenario of organ transplants in Brazil between the years 2018 and 2022. Descriptive study of quantitative approach, with data from the Department of Informatics and Brazilian Registry of Transplants, made available by the National Transplant System, with graphical analysis of numerical variables of notifications of potential donors, amount transplants and family refusal, in the period between 2018 and 2022. In the study period, 58,222 potential donors and 17,367 effective donations were registered, Brazil occupies the fourth position in kidney and liver transplantation. As for potential donors, the South region stands out with higher notifications and the North and Northeast regions with lower notifications. Regarding the notifications of effective donors, the South region took the lead in terms of notifications, while the North region has the lowest rates, but in 2022 it stands out with a notable increase. Regarding the number of transplants, the kidney stands out as the largest transplanted organ, on the other hand the intestine and multivisceral organs have limited numbers in the period analyzed. Finally, family refusals showed variations between the study period and there was a significant increase in 2022. The transplantation scenario in Brazil shows advances, but also challenges. Despite progress in donor rates in certain regions, the disparity between demand and availability, along with cultural and information issues, impacts the system. Awareness, education and health policies are vital to ensure the accessibility and viability of organ donation.